Istrātījiyyat al-Umm allatī Tuʿāṭifu ar-Raʾīs al-Jumhūriyyah fī asy-Syiʿr Risālat al-Umm li Raʾīs al-Jumhūriyyah li Īfī Adāwatī bi Naẓariyyat as-Sayṭarah li Anṭūniyū Grāmshī - Abdul Basith Waliya Apriliyanti (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
Hegemony is one of the most influential theories developed by Antonio Gramsci in the field of literary studies. The poem A Mother's Letter to the President is closely related to Gramsci's theory of hegemony because it addresses socio-political and economic issues that occurred in Yogyakarta while portraying the struggles of a mother and her family. This study aims to investigate the events that reflect the mother's strategies in appealing to the President's sympathy in the poem A Mother's Letter to the President by Ifi Adawati through the perspective of Gramsci's theory of hegemony. It also seeks to examine the meanings of these events using the framework of the sociology of literature. To answer the research questions, the researcher employs four analytical concepts derived from Gramsci's theory: the concept of culture, the concept of hegemony, the concept of ideology, the concept of common beliefs, and the concept of common sense. These concepts are used to reveal the forms of hegemony embedded in the poem. The findings indicate that the poem contains representations of culture, hegemony, ideology, common beliefs, and common sense. It also portrays hegemonic tensions experienced in Yogyakarta, particularly through the depiction of a mother who struggles to provide higher education for her children despite severe financial hardship. She hopes that free education will enable her children to pursue a better future while also highlighting women's rights and the hardships they endure. Ultimately, the poem expresses the mother's appeal to the President to improve her family's destiny through educational opportunities for her children.